Modeling of optimum chiral carbon nanotube using DFT - Farhana, Soheli; Alam, A. H. M. Zahirul; Khan, Sheroz; Motakabber, S. M. A. (2013)
The geometrical structure of carbon nanotubes has been calculated and analyzed in this paper. The analysis of carbon nanotube for Pz orbital, perpendicular to the graphene sheet and thus the nanotube surface forms a delocalized π network across the nanotube, which is responsible for its electronic properties. These electronic properties are obtained from tight binding (TB) model for graphene. Furthermore, optimized DFT calculation shows the optimum chiral of CNT, which is semiconducting zigzag for SWCNT and MWCNT.